PENGARUH KONSENTRASI BUBUR BUAH DAN TEPUNG KEDELAI (Glycine max) TERHADAP KARAKTERISTIK FIT BAR BLACK MULBERRY (Morus nigra L.) - Yusman Taufik (Department of Food Technology, Universitas Pasundan, Bandung, 2018)
The purpose of this research is to determine the consentration of fruit’s pulp and soy powder of fit bar black mulberry. The model of experimental design that is used in this research is Randomized Block Design (Group) RAK with 2 factors and 3 time repetitions, so it obtained 27 units of the experiment, where the factors include: the effect of the concentration of fruit’s pulp (A), which consists of three levels, a1 (5%), a2 (10%), a3 (15%) and concentrations of soy powder (B) consisting of 3 levels: b1 (14%), b2 (16%), b3 (18%). The response in this study is chemical response, which is protein content, carbohydrate content, and fat content, physical response is hardness. Organoleptic response include color, flavor, and texture, and then antioxidant activity for selected sample. The selected sample is a3b3 (15% fruit pulp concentration and 18% soy flour concentration), it has 43.21% of carbohydrate content, 11.53% of protein content, 9.23% of fat content, 2.15 mm/sec/100 grams of hardness, and 139.480 ppm of antioxidant activity (average).